Profesionalisme Guru Agama Kristen Dalam Pembentukan Karakter Peserta Didik - Roseta, Roseta; Sirait, Junio Richson (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2022)
Teachers are educators, and it can be said that teachers are people who play a very important role in producing humans with good quality human resources for the country. The phenomena obtained from the teachers slapping and tearing students' books for not doing their assignments. The aims of this research are as follows: (1) what is meant by a professional teacher? (2) how is the character of Christian religious education teacher? (3) how is the competence of Christian religious education teacher? (4) how to shape the character of student? and (5) How is the professionalism of Christian religious educators to shape the characteristics of students? This research uses a qualitative method with a literature study approach. The results of the study are (1) Professional teachers are educators who do work as educators/teachers with high capacities who are the source of life. (2) Have the characters of Christ. (3) Have pedagogic, professional, social, and personality competencies. (4) An exemplary teacher. (5) a teacher who has the principle that students are gold, gems and diamonds that do not pay off. Guru merupakan tenaga pendidik, dan bisa dikatakan guru adalah orang yang sangat berperan dalam mengasilkan manusia dengan kualitas sumber daya manusia yang baik bagi negeri. Fenomena yang di dapatkan Guru menampar dan merobek buku murid hanya karena tidak mengerjakan tugas. Tujuan penelitian ini adalah sebagai berikut: (1) Apakah yang dimaksud guru professional? (2) Bagaimana karakter guru pendidikan agama Kristen? (3) Bagaimana kompetensi guru pendidkan agama Kristen? (4) Bagaiman membentuk karakter peserta didik? dan (5) Bagaimana Profesionalisme tenaga pendidik agama kristen untuk membentuk karaktersitik peserta didik? Penelitian ini menggunakan metode kualitatif dengan pendekatan studi pustaka. Hasil dari penelitian adalah (1) Guru Profesional merupakan pendidik yang melakukan pekerjaan sebagai pendidik/pengajar dengan kapasitas tinggi yang menjadi sumber kehidupan. (2) Memiliki karakter Kristus. (3) Memiliki kompetensi pedagogic, profesional, sosial, dan kepribadian. (4) Guru yang menjadi teladan. (5) Guru yang memiliki prinsip bahwa peserta didik adalah emas, permata dan berlian yang tidak terbayar harganya.